2021
DOI: 10.1158/2159-8290.cd-20-0571
|View full text |Cite
|
Sign up to set email alerts
|

TRK xDFG Mutations Trigger a Sensitivity Switch from Type I to II Kinase Inhibitors

Abstract: discussed the modelling experiments and analyses, S.K. carried out the modelling experiments.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 47 publications
2
52
0
2
Order By: Relevance
“…Preclinical study showed that DS-6051b was significantly effective in inhibiting NTRK and ROS1-rearranged cancers, as well as TKI-resistant tumors with secondary kinase domain mutations, such as G2032R mutation in ROS1 and G595R mutation in NTRK1 ( 103 ). However, NTRK1 G667C mutation was resistant to DS-6051b; it was consistent with previous reports claiming G667C mutation in xDFG motif being resistant to next-generation TRK inhibitors ( 93 , 103 ). Preliminary clinical activity of DS-6051b was observed in TKI-naive and crizotinib-pretreated ROS1+ NSCLC patients and a patient with TPM3-NTRK fusion-positive thyroid cancer who achieved a confirmed partial response of 27 months at the last follow-up ( 104 , 105 ).…”
Section: Trk Inhibitors and Resistancesupporting
confidence: 92%
See 2 more Smart Citations
“…Preclinical study showed that DS-6051b was significantly effective in inhibiting NTRK and ROS1-rearranged cancers, as well as TKI-resistant tumors with secondary kinase domain mutations, such as G2032R mutation in ROS1 and G595R mutation in NTRK1 ( 103 ). However, NTRK1 G667C mutation was resistant to DS-6051b; it was consistent with previous reports claiming G667C mutation in xDFG motif being resistant to next-generation TRK inhibitors ( 93 , 103 ). Preliminary clinical activity of DS-6051b was observed in TKI-naive and crizotinib-pretreated ROS1+ NSCLC patients and a patient with TPM3-NTRK fusion-positive thyroid cancer who achieved a confirmed partial response of 27 months at the last follow-up ( 104 , 105 ).…”
Section: Trk Inhibitors and Resistancesupporting
confidence: 92%
“…LOXO-195 possessed poor penetration into the brain because of the blood–brain barrier and multidrug efflux transporters, such as ABCB1 and ABCG2 ( 91 , 92 ). In addition, clinical evidences and preclinical findings revealed that TRKA xDFG motif substitutions, such as TRKA G667A and TRKA G667C, conferred resistance to the next-generation TRK inhibitors including selitrectinib and repotrectinib through impaired drug binding ( 93 ). Recently, a case report showed that a patient with DCTN1-NTRK1 fusion-positive undifferentiated pleomorphic sarcoma did not respond to LOXO-195 who harbored acquired NTRK1 G667C mutation after disease progression with larotrectinib ( 94 ).…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…As with other tyrosine-kinase inhibitors, resistance can develop over time in patients receiving TRK inhibitors. Point mutations in the NTRK-kinase domain have emerged as an important mechanism of resistance, including G667C in NTRK1 and G696A in NTRK3 28 . Activation of the MAPK signaling pathway through hotspot mutations in KRAS and BRAF and amplification of MET have caused acquired resistance to first-generation TRK inhibitors in gastrointestinal cancers 29 .…”
Section: Ntrk Molecular Aberrationsmentioning
confidence: 99%
“…Structurally, the conformationally constrained macrocyclic inhibitors and 4 can well accommodate the bulky TRKA G595R mutant at the solvent front without any steric clashes. However, recent clinical ndings indicate that therapeutic e cacy of both drugs can be compromised by the TRKA G667C mutant in xDFG motif, as the resulting steric hindrance between the mutant and the restricted uorinated aromatic moieties in and 4 reduce binding a nity of drugs to protein 23 . To date, there are no approved drugs for treatment of patients who had developed resistance to 1 and 2 resulting from TRKs kinase secondary mutations.…”
Section: Introductionmentioning
confidence: 99%